IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT BY ACTIVATING GROUP WORKS IN SECONDARY SCHOOL - Mochamad Ardi Setyawan; St. Shabibatul Rohmah; Mahfud (SOSIOEDUKASI, 2023)
The aim of writing this paper is to find out the importance of learning English at school. Writing the paper uses the literature review method (library research). From the discussion it can be concluded that learning English at school is very important. The learning method that is very often used is CLT because it is effectively used as a method in the English language teaching and learning process. This is based on the communication skills obtained by students, not just mere knowledge, students will be motivated and feel that something they have learned can be useful and used in language.